ナンキョク ミズホ キチ ニ オケル ヒセツ ノ サンソ ドウイタイ ソセイ ノ ネン ヘンカ ト セキセツ ソウ ノ ドウイタイ ソセイ - 上田, 豊; アゲタ, ユタカ; Ageta, Yutaka (1993)
P(論文) 南極の斜面下降風域で, 積雪層を形成する前段階の新しいドリフトの試料をほぼ1年間にわたって採取し, それらの酸素同位体組成を測定した。また, 同地点の積雪層の同位体プロファイルも得られた。ドリフトのδ^<18>O値は, 夏に高く(-30～-40‰), 冬は-50‰近くまで下がる場合があるが, 時々夏なみに高かった。δ^<18>O値と試料採取時の気温との関係はばらつき, 試料の起源の相違のためか, 採取時の気象状態によってずれた。もしこれらのドリフトが連続的に堆積すれば, 積雪層のδ^<18>O値の鉛直プロファイルも広い幅で複雑な変化をするはずだが, 実際は-35～-45‰の範囲で単調に変化する。このプロファイルの極大・極小位置は, 堆積中断で形成された氷板の分布と良い相関がある。これらの結果は, 雪の同位体組成の堆積後の変化が, 積雪の同位体プロファイルの理解に重要なことを示している。 Oxygen isotopic contents of fresh snow drifts in the katabatic wind zone were measured. The samples were collected at a stage before forming deposited snow layers throughout the year. Besides, the oxygen isotope profiles of deposited snow layers at the same place were obtained. The δ^<18>O contents of the snow drifts had high values in summer (-30～-40‰); in winter, values were generally low (above -50‰) but sometimes there were high values similar to those in summer. Deviation of relations between air temperature at sampling time and δ^<18>O contents of the snow drifts under different weather conditions is discussed. Vertical profiles of δ^<18>O contents of deposited snow are supposed to show a wide annual range and complicated annual variation, if such snow drifts accumulated continuously. However, those of deposited snow actually seen in the surface layers usually show a narrow range (-35～-45‰) and simplified pattern. Positions of maxima and minima in δ^<18>O profiles of deposited snow have good correlations with layering of ice crusts which were formed during hiatus periods of snow deposition. These results indicate the importance of change of the isotopic contents after snow deposition for understanding the isotope profiles of deposited snow. departmental bulletin paper